Entre ritos e mitos: a Romaria da Nossa Senhora Medianeira de Todas as Graças, em Santa Maria, RS - Silva, Larissa Molinos da (2011)
This text is to the observation and analysis of the importance of the Romaria da Nossa Senhora Medianeira de Todas as Graças for the city of Santa Maria - RS, and how she became a saint of popular devotion. Through an ethnographic study conducted between the years 2009 and 2010, with different actors, such as: the local Catholic Church, local faithful people, pilgrims and tourists; seeking to interpret the different motivations for the participation in the Pilgrimage. And at last, a reflection is carried on how this religious event through its myth and ritual influences on the development of religious tourism in the city of Santa Maria-RS.